IoT Based Environmental Monitoring System for Residential Building with LoRa Technology - Zin Mar; Lwin, Zin Mar; Hla, Tin Tin (The Indonesian Journal of Computer Science, 2025)
This paper introduces an environmental monitoring system for residential buildings that combines PIC microcontroller functionality with LoRa technology. The system integrates motion, flame, gas, vibration, temperature, and humidity sensors to provide real-time monitoring of environmental conditions and safety risks. The PIC microcontroller acts as the system's core, gathering and processing data from the sensors before transmitting it over a LoRa network to a remote station. LoRa technology is employed for its long-range and low-power communication capabilities, making the system energy-efficient and reliable for residential applications. By delivering timely alerts and insights into potential hazards, this system enhances safety and livability in residential settings. The results highlight the practicality of the proposed design and its potential for integration into smart building applications, offering a scalable and efficient solution for modern environmental monitoring challenges.